PREVALANCE OF PREMENSTRUAL SYNDROME AND KNOWLEDGE ASSESSMENT REGARDING IT’S PREVENTION AMONG MEDICAL STUDENTS OF A PRIVATE MEDICAL COLLEGE OF ISLAMABAD: Premenstrual Syndrome And It’s Knowledge - Kalsoom, Dr Umay; Sultana, Abida; Amjad, Tahira; Bairam, Saima (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess prevalence of premenstrual syndrome (PMS) in medical students and to determine theirknowledge regarding its prevention.Study Design: A cross sectional study.Place and Duration of Study: This study was conducted at Foundation University Medical College, Islamabad,from Jun to Aug 2017.Material and Methods: A purposive sample of 359 female medical students was taken after applying selectioncriteria. After ethical approval and consent of respondents, data was collected through self-administeredstructured questionnaire on demographic variables, prevalence of PMS, physical, psychological and behavioralchanges, knowledge regarding its prevention etc. Data was analyzed by SPSS version 20. Frequencies werecomputed and descriptive statistics applied. Cross tabulation between knowledge regarding prevalence ofpremenstrual syndrome and prevention of premenstrual syndrome was done. Pearson Chi Square test wasapplied to see the association between these two variables. Cochran test of conditional independence was appliedto see conditional association between these variables at p-value